2021
DOI: 10.14814/phy2.14925
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal intake of omega‐3 promotes Wnt/β‐catenin signaling pathway, and preserves integrity of the blood–brain barrier in preeclamptic rats

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 61 publications
1
4
0
Order By: Relevance
“…Also, Zhang et al revealed disturbed integrity of the BBB due to loss of tight junction proteins in neonatal and adult mouse models of cerebral ischemia [ 66 ]. In a PE rat model, it is shown that PE induced a cascade of neuroinflammation and oxidative injury to the BBB [ 67 ], which is in accordance with the findings in this study. As shown in Lara et al's study, cognitive alterations present in children born from preeclamptic pregnancies are strongly associated with impaired cerebral Vegf levels and changed angiogenesis phenotype, a finding which is also seen in this study with lower levels of Vegfd upon hsFLT1 overexpression [ 25 ].…”
Section: Discussionsupporting
confidence: 91%
“…Also, Zhang et al revealed disturbed integrity of the BBB due to loss of tight junction proteins in neonatal and adult mouse models of cerebral ischemia [ 66 ]. In a PE rat model, it is shown that PE induced a cascade of neuroinflammation and oxidative injury to the BBB [ 67 ], which is in accordance with the findings in this study. As shown in Lara et al's study, cognitive alterations present in children born from preeclamptic pregnancies are strongly associated with impaired cerebral Vegf levels and changed angiogenesis phenotype, a finding which is also seen in this study with lower levels of Vegfd upon hsFLT1 overexpression [ 25 ].…”
Section: Discussionsupporting
confidence: 91%
“…And the study population with a relatively small sample size needs to be considered during drawing a conclusion on the status of serum sVEGFR-1 in patients with several types of clinical presentation of PE. Recently, various pharmacological agents that can prevent the effects of sVEGFR-1 for treating PE have been investigated ( 27 , 28 , 29 ) . These agents may have a significant effect on reducing neonatal morbidity and mortality, given that they are considered safe enough to delay delivery for several weeks and alleviate end-organ findings.…”
Section: Discussionmentioning
confidence: 99%
“…L-NAME (50 mg/kg/day; Sigma-Aldrich ( 30 , 101 )) or phosphate buffered saline (PBS; 137 mM NaCl, 10 mM Na 2 HPO 4 , 1.8 mM KH 2 PO 4 , and 2.7 mM KCl, pH 7.4) as control was administered daily from embryonic day (E)7.5 to E17.5 of pregnancy (approximately early second trimester to term in human equivalent to model early onset disease) via 100 μl subcutaneous injection. On E14.5 and E17.5 of pregnancy, urine was collected (spot collection on/upon handling), and blood pressure measured.…”
Section: Methodsmentioning
confidence: 99%